LINGUISTIC FEATURES OF THE CANARY DIALECT IN THE CONTEXT OF THE SPANISH-SPEAKING COUNTRY - Bugayova , Catherine (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
The article deals with the the main linguistic features of the Canary dialect, historical and socio-cultural factors that influenced its emergence and further development. As one of the main difficulties in mastering Spanish is the variety of national variants and dialects of Spanish, this article deals with the Canary language as a separate dialect area, with its peculiarities of functioning and considers its relationship with the norm of the Castilian version of Spanish.__________References:• Danilenko, A. A. «Problema jazykovoj situacii v Ispanii.» Issledovanija molodyh uchenyh, http://dspace.nbuv.gov.ua/bitstream/handle/123456789/92786/30-Danylenko.pdf?sequence=1• Moskalenko, A. S. El aporte portugues al vocabulario canario (2013), http://irbis-nbuv.gov.ua/cgi-bin/irbis_nbuv/cgiirbis_64.exe?C21COM=2&I21DBN=UJRN&P21DBN=UJRN&IMAGE_FILE_DOWNLOAD=1&Image_file_name=PDF/psptkl_2013_23_65.pdf• José Miguel Alzola. Breve historia de las Islas Canarias. (Gran Canaria, 1991): 16-21; 48-57, https://mdc.ulpgc.es/utils/getfile/collection/MDC/id/85618/filename/123062.pdf• Almeida Suárez. El concepto de ‘hablas de tránsito’ y el español canario (2013), https://core.ac.uk/download/pdf/38842119.pdf• Lorena, A. De-Matteis. Sobre el concepto de seguridad lingüística: propuesta de formulación para contextos institucionales específicos, 2-3.
Keywords: Spanish language, Canary dialect, territorial variant of language, territorial dialect, dialect variability